Assessing the therapeutic potential of vagus nerve stimulation in autoimmune diseases: A systematic review - Eubi Chan; Ali R. Mani (Physiological Reports)
Abstract Emerging evidence suggests that the vagus nerve can modulate the immune system in experimental settings. Vagus nerve stimulation (VNS), initially developed for managing epilepsy, is now being explored as a treatment for autoimmune diseases due to its potential immunomodulatory effects. This systematic review evaluates the therapeutic potential of VNS in autoimmune diseases by critically appraising findings from human clinical studies. This systematic review was conducted in accordance with the PRISMA guideline, with a comprehensive literature search performed in Ovid, Cochrane, and PubMed databases up to July 2024. Studies focusing on VNS in patients with autoimmune diseases were eligible, and the quality of study was assessed using the QualSyst tool. Of the 53 papers identified for full‐text assessment, 19 studies met the eligibility criteria. Findings suggest that VNS is a promising adjunctive therapy for Crohn's disease and rheumatoid arthritis, showing potential to alleviate symptoms and modulate immune responses. The efficacy and safety of VNS vary widely across studies, highlighting the complex nature of autoimmune diseases and the diverse mechanisms of VNS action. Future research should prioritize large‐scale, randomized controlled trials with standardized protocols to further elucidate the efficacy, long‐term safety, and optimal parameters of VNS across various autoimmune conditions.